2014
DOI: 10.1001/jamaneurol.2014.2057
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil in the Treatment of Neuromyelitis Optica Spectrum Disorder

Abstract: IMPORTANCE Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory disorder of the central nervous system. Recently, various immunosuppressant medications were introduced as therapeutic options for preventing relapse of NMOSD. However, our understanding of the effectiveness of mycophenolate mofetil (MMF) in treating patients with NMOSD is based on only a small number of studies.OBJECTIVE To evaluate the efficacy and safety of MMF treatment in patients with NMOSD. DESIGN, SETTING, AND PARTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 29 publications
(40 reference statements)
8
78
0
3
Order By: Relevance
“…While therapeutic interventions with immunosuppressive drugs can reduce the frequency of NMO relapses, 3,[7][8][9][10][11] individual patients in most studies did not respond sufficiently to treatment or experienced major adverse effects. Therefore, better preventive NMO therapies are desirable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While therapeutic interventions with immunosuppressive drugs can reduce the frequency of NMO relapses, 3,[7][8][9][10][11] individual patients in most studies did not respond sufficiently to treatment or experienced major adverse effects. Therefore, better preventive NMO therapies are desirable.…”
Section: Discussionmentioning
confidence: 97%
“…3 However, relapse prevention remains a challenging issue in NMO because established multiple sclerosis therapies such as interferons, natalizumab, and fingolimod have been reported to show little efficacy or even to be detrimental. [4][5][6] According to smaller case series or retrospective cohort studies, long-term immunosuppression with azathioprine 7 or mycophenolate mofetil 8 is recommended for mild NMO cases, with methotrexate being an alternative treatment option. 3,9 In patients with more severe NMO courses, rituximab 10 and mitoxantrone hydrochoride 11 have been reported to diminish the relapse frequency.…”
mentioning
confidence: 99%
“…Theoretically, the absence of attack-related inflammation could also release repair processes such as remyelination. Indeed, several studies investigating broad or selective immunosuppression reported an improvement of disability during the course of treatment [21,81,83,84,87,92,102,121,122].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits lymphocyte proliferation by suppression of guanosine nucleotide biosynthesis and is used for psoriasis, proliferative lupus nephritis, and renal transplant rejection. Four retrospective cohorts evaluating 24-58 patients with mostly AQP4-IgG-positive NMOSD have reported beneficial outcomes of MMF therapy with or without concomitant corticosteroids [79,81,83,84]. MMF treatment for a median of 20-27 months resulted in a reduction of the ARR by 80-93 % and improvement of the median EDSS in 3/ 4 studies (not reported in 1).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
See 1 more Smart Citation